The Paradoxical Effect of Inclusive Leadership on Subordinates’ Creativity - Zhu, Jinqiang; Xu, Shiyong; Zhang, Bainan (Frontiers in Psychology, 2020)
Previous research about inclusive leadership and creativity has produced contradictory results. The present study tried to explain the contradictory findings based on the antecedent-benefit-cost framework (ABC). We found that inclusive leadership promoted subordinates’ creativity by enhancing subordinates’ psychological safety but discouraged subordinates’ creativity by reducing challenge-related stress. The present study illustrated the complex mediating mechanism of inclusive leadership’s impact on creativity, presenting a complementary explanation of the conflicting relationships between inclusive leadership and creativity. In addition, we validated the ABC framework.